La violence seigneuriale à la fin du Moyen Âge, vue par les représentations pédagogiques en France - Pierre Prétou (Criminocorpus)
The use of pictures to teach the medieval seigniory in France turns the lessons of history into a weird morale teaching. The iconography deployed, continuously since the Second World War, insert systematically crude or discreet representations of violence at the heart of the lordship system. Despite decades of scholarship efforts, the resilience of this portrayal demonstrates the power of the pictures over our collective knowledge. It shows up as well the weakness of the critical tools used over the imaging thought. A major confusion between village and lordship is clearly at the origin of it, which explains at the end an education in good and in evil, developed through the ages of life that replaces the teaching of historical science.